2021
DOI: 10.1021/acsami.1c06846
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Universal Approaches for Cavity Regulation during Cylinder Impact Processes for Drag Reduction in Aqueous Media: Macrogeometry Vanquishing Wettability

Abstract: Stabilizing lubricating gas films at the solid–liquid interface is a promising strategy for underwater drag reduction. It has been restricted by the enormous extra energy input and the poor stability of superhydrophobic coatings. Cavity encapsulation is a valid method to improve and maintain the formation of the air layer on the solid surface, which is created by the rapidly impacting process on a water surface. The wettability of solid objects (the combination of the surface roughness and chemical component) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…32 Hydrophilicity is an important feature that influences cell attachment, migration, and viability. 33 Our hydrophilicity measurements showed that both 2D and 3D conduits had reasonable hydrophilicity, but especially the 3D ones (Figure 2B).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…32 Hydrophilicity is an important feature that influences cell attachment, migration, and viability. 33 Our hydrophilicity measurements showed that both 2D and 3D conduits had reasonable hydrophilicity, but especially the 3D ones (Figure 2B).…”
Section: Resultsmentioning
confidence: 70%
“…One possible reason is that the characteristic absorption band of imine (CN) formed by cross-linking reaction overlapped with the strong absorption band of the amide I in SF . Hydrophilicity is an important feature that influences cell attachment, migration, and viability . Our hydrophilicity measurements showed that both 2D and 3D conduits had reasonable hydrophilicity, but especially the 3D ones (Figure B).…”
Section: Resultsmentioning
confidence: 89%
“…Reduction of fluid resistance is of significance to increasingly emerging energy and environmental issues. Turbulence is the major source of fluid resistance in many cases and has attracted extensive attention. Hence, research into drag reduction has focused on methods to depress turbulence near walls. Biomimetic riblet surfaces, such as blade, wavy, sinusoidal, and herringbone riblet (Blade, Wavy, Sinusoidal, and Herringbone, respectively) surfaces, inspired by sharks and birds have achieved significant reductions in turbulent drag reduction. Blade surfaces have been proven to provide obvious drag reduction, and they have shown promise for many potential applications in the pipeline, aircraft, energy, and transportation industries. , …”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Consequently, for hydrodynamic drag reduction, it is essential to reduce the form of drag on a blunt body.The innovative approach of form drag reduction is realized by changing the shape of the blunt body to a streamlined body through introducing a cavity. [3][4][5][6][7] The cavity can be generated by the principle of natural cavitation on underwater objects because the water near the head of the object is vaporized to generate cavitation when the speed of the object is high enough. [8,9] However, at low speeds, the cavity greatly depends on the air-capture process when the object impacts the water surface.…”
mentioning
confidence: 99%
“…On a blunt body, the form of drag underwater is much greater than the skin friction. [3,4] Consequently, for hydrodynamic drag reduction, it is essential to reduce the form of drag on a blunt body.…”
mentioning
confidence: 99%